Assessment of Flood Hazard and Agriculture Damage Under Climate Change in the Bagmati River Basin of Nepal - Bhakta Shrestha, Badri (International Journal of Environment, 2019)
Assessment of flood hazard and damage is a prerequisite for flood risk management in the river basins. The mitigation plans for flood risk management are mostly evaluated in quantified terms as it is important in decision making process. Therefore, analysis of flood hazards and quantitative assessment of potential flood damage is very essential for mitigating and managing flood risk. This study focused on assessment of flood hazard and quantitative agricultural damage in the Bagmati River basin including Lal Bakaiya River basin of Nepal under climate change conditions. Flood hazards were simulated using Rainfall Runoff Inundation (RRI) model. MRI-AGCM3.2S precipitation outputs of present and future climate scenarios were used to simulate flood hazards, flood inundation depth, and duration. Flood damage was assessed in the agricultural sector, focusing on flood damage to rice crops. The flood damage assessment was conducted by defining flood damage to rice crops as a function of flood depth, duration, and growth stage of rice plants and using depth-duration-damage function curves for each growth stage of rice plants. The hazard simulation and damage assessment were conducted for 50- and 100-year return period cases. The results show that flood inundation area and agricultural damage area may increase in the future by 41.09 % and 39.05 % in the case of 50-year flood, while 44.98 % and 40.76 % in the case of 100-year flood. The sensitivity to changes in flood extent area and damage with the intensity of return period was also analyzed.